THE ROLE OF MADRASAH IBTIDAIYAH TEACHER EDUCATION DEPARTMENT STUDENTS (PGMI)-4 UINSU IN COMMUNITY SERVICE TOWARDS THE EDUCATION FIELD AT TANJUNG MULIA - Nurpusfita Sari; Lailatussyifa Lailatussyifa; Nadia Rahmi; Siti Munawaroh; Luthfiyah Zulfaini Silalahi; Andina Halimsyah Rambe (Academy of Education Journal, 2023)
Students are the cornerstone of the country’s development. While we are students, we must remember that we have a huge responsibility to contribute to the realization of the Tri Dharma of Higher Education. One of the main pillars of the Tri Dharma of Higher Education is community service. Community service is the direct implementation of science, technology, and cultural arts to the community through scientific methodologies as the dissemination of the Tri Dharma of Higher Education and noble responsibilities in an effort to develop community capabilities, so as to accelerate the growth rate of achieving national development goals. This study is aimed to describe the role of PGMI 4 UINSU students in education field. The PGMI 4 UINSU students work programs in education focus on maghrib mengaji, teaching at MDTA and distributing sirah nabawiyah books. In this study, the researchers used a qualitative approach with observation and description methods. The participants of this study were the children in Tanjung Mulia, particularly MDTA students and local community. The result shows that in terms of education, the children lack of discipline and motivation, so they are possibly find it hard to develop their creativity. In addition, in terms of maghrib mengaji and distributing sirah nabawiyah books, it has been done successfully. Furthermore, students have a role as the facilitators and drivers of programs implementation